Inovasi Rancang Bangun Sistem Panel Surya Pintar dengan Sistem Solar Tracking Otomatis Berbasis Mikrokontroler Arduino Uno - Ambabunga, Yusri; Saka, Bergita Gela; Pebriawant, Sardie (Syntax Corporation, 2026)
The development of renewable energy technology encourages innovation in improving the efficiency of photovoltaic systems, one of which is through the application of an automatic solar tracking smart solar panel system. This research aims to design and build a smart solar panel system using an Arduino Uno microcontroller that is able to follow the movement of the sun in real-time. This system utilizes a Light Dependent Resistor (LDR) sensor to detect light intensity and control the actuator in the form of a servo motor or stepper in regulating the position of the panel on two axes (dual-axis). Based on various studies, Arduino-based solar tracking systems have been proven to be able to significantly increase the efficiency of solar energy absorption compared to static panels, with an increase in output power ranging from 20% to 40% (Pardosi et al., 2024); (Al-Chlaihawi et al., 2024); (Ingle, 2025). This increase occurs because the panels are always at an optimal angle to solar radiation (Mohamad et al., 2021); (Hassan & Abubakar, 2020). The implementation of the Arduino Uno microcontroller-based system provides advantages in terms of cost, ease of programming, and development flexibility (Pawar et al., 2025); (Shahrier et al., 2023). Thus, the design and construction of this system is expected to be an innovative solution in improving solar energy efficiency and supporting the development of sustainable clean energy technology. The implementation of the Arduino Uno microcontroller-based system provides advantages in terms of cost, ease of programming, and development flexibility (Pawar et al., 2025); (Shahrier et al., 2023). In addition, the system also allows integration with Internet of Things (IoT) technology for remote performance monitoring and continuous operational optimization. Thus, the design and construction of this system is expected to be an innovative solution in improving solar energy efficiency and supporting the development of sustainable clean energy technology.